Mean and Bold? - Kristof De Witte; Elbert Dijkgraaf (Tinbergen Institute, 2007)
The Dutch drinking water sector experienced two drastic changes over the last 10 years. Firstly, in 1997, the sector association started with a voluntary benchmarking aimed to increase the efficiency and effectiveness of the sector. Secondly, merger activity arose. This paper develops a tailored nonparametric model to dissect and distinguish the effects on efficiency of these two evolutions. In particular, we adapt Free Disposal Hull (FDH) to estimate robust and conditional non-oriented efficiency estimates. Parametric COLS (Fourier) tests show the robustness of the model with respect to the specification and its variables. We classify the merger economies into scale economies and increased incentives to fight inefficiencies. Although we detect a significant efficiency enhancing effect of benchmarking, we find insignificant merger economies due to the absence of scale economies and the absence of increased incentives to fight inefficiencies.
Keywords: C13; C14; D20; G34; L95; 330; Mergers and acquisitions; efficiency; scale economies; water sector; non-parametric and parametric estimation; Benchmarking; Übernahme; Wasserwirtschaft; Skalenertrag; Wirtschaftliche Effizienz; Nichtparametrisches Verfahren; Niederlande